All the world beside - Conley, Garrard (Riverhead Books, 2024)
"Cana, Massachusetts: a utopian vision of 18th-century Puritan New England. To the outside world, Reverend Nathaniel Whitfield and his family stand as godly pillars of their small-town community, drawing Christians from across the New World into their fold. One such Christian, physician Arthur Lyman, discovers in the minister's words a love so captivating it transcends language. As the bond between these two men grows more and more passionate, their families must contend with a tangled web of secrets, lies, and judgments which threaten to destroy them in this world and the next. And when the religious ecstasies of the Great Awakening begin to take hold, igniting a new era of zealotry, Nathaniel and Arthur search for a path out of an impossible situation, imagining a future for themselves which has no name. Their wives and children must do the same, looking beyond the known world for a new kind of wilderness, both physical and spiritual. Set during the turbulent historical upheavals which shaped America's destiny and following in the tradition of Nathaniel Hawthorne's The Scarlet Letter, All the World Beside reveals the very human lives just beneath the surface of dogmatic belief. Bestselling author Garrard Conley has created a page-turning, vividly imagined historical tale that is both a love story and a crucible"--